Global and regional left ventricular deformation evaluation with feature tracking in transthyretin cardiac amyloidosis. Comparison with echocardiographic findings. (3rd October 2022) - Bastidas Plaza, D; Pozo Osinalde, E; Islas, F; Perez De Isla, L; Marcos-Alberca, P; Hernandez, P; Martin-Lores, I; Luaces Mendez, M; Gomez De Diego, J J; Bustos, A; Perez-Villacastin, J; De Agustin, J A
Abstract: Background: Diagnosis of cardiac amyloidosis (CA) is basically based on imaging techniques. Transthoracic echocardiography (TTE) is crucial to raise suspicion of this disease through detection of the classical features. An specific left ventricular (LV) deformation pattern with apical sparing ("cherry on top") has been described on speckle tracking (ST) TTE. However, there is no data regarding the role of the LV global and regional analysis with the new tool feature tracking (FT) of cardiac magnetic resonance (CMR) in CA. Purpose: Our aim is to analyze the concordance of LV deformation between ST-TTE and FT-CMR. Methods: Consecutive patients with definitive diagnosis of transthyretin (TTR) CA, based on DPD scintigraphy, and imaging evaluation with TTE and CMR were retrospectively included. LV volumes and ejection were calculated from both TTE and CMR following the ongoing recommendations. Global and segmental longitudinal strain values were obtained from apical 2-, 3- and 4-chambers projections on TTE, while the same parameters were calculated on the same cine views of CMR using a dedicated software of FT analysis. Student t-test was used to compared mean measurements derived from both imaging techniques. Apical index was calculated as the ratio between apical and basal-mid longitudinal values. Moreover, agreement was established using Passing-Bablok regression analysis. Results: 27 patients (80 years-old, 88% men) with definitive diagnosis of TTR CA from our tertiary hospital were included. Regarding echocardiographic findings, 80% showed concentric LV hypertrophy with low normal ejection fraction in the majority (52±10%). When longitudinal LV strain parameters were compared (Table 1), no differences were noted in global and apical values whereas basal and mid measurements were higher from CRM resulting in different apical indexes. Although 42% showed a typical "cherry on top" pattern in ST analysis, in only 18% of the FT apical sparing was detected. Consistently, decremental pattern was observed in 60% of TTE and in 20% of CMR. Concordance analysis with Passing-Bablok showed no constant or proportional differences, meaning both techniques were comparable. Conclusions: Among patients with TTR CA there were no differences in global longitudinal LV strain analysis between ST-TTE and FT-CMR. Nevertheless, discordance in regional parameters resulted in a less frequent detection of apical sparing in CMR. Funding Acknowledgement: Type of funding sources: None.